Keberadaan Lalat dan Parasit Usus di Permukiman pada Kawasan TPA Talang Gulo Jambi - Susy Ariyani Arif; Suhermanto Suhermanto; Krisdiyanta Krisdiyanta (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Flies are mechanical vectors which can transmit diseases. The aim of the study was to identify various fly and intestinal parasite species in the settlements near Talang Gulo waste final disposal site of Jambi in 2018. The study method is analytical descriptive analytic with observational and cross sectional approaches. The study results show that the species of the caught flies are: small house flies (Fannia spp) 6.3 %, meat flies (Sarcophaga spp) 6.3 %, green flies(Calliphoridae) 15.6 %, and house flies (Musca domestica) 71.9 %. The fly density was measured as much as 16, which is categorised as high (density between 6-20). In the active zone of Talang Gulo, at the third point, two fly species was found carrying intestinal parasites Ascaris lumbricoides, i.e. Musca domestica (19 %) and Chrysomya megacephala (1 %). Those intestinal parasites were only found in garbage in the active zone at point one, point two and point three (25 %). Based on the study results, the garbage officers of Talang Gulo are recommended to wear gloves to prevent contamination from Ascaris lumbricoides’s eggs. Fly control at the wastesite should be also in concern, particularly in the nearby settlements.